2009
DOI: 10.1088/0004-637x/693/1/l11
|View full text |Cite
|
Sign up to set email alerts
|

STEREO OBSERVATIONS OF ENERGETIC NEUTRAL HYDROGEN ATOMS DURING THE 2006 DECEMBER 5 SOLAR FLARE

Abstract: We report the discovery of energetic neutral hydrogen atoms (ENAs) emitted during the X9 solar event of 2006 December 5. Beginning ∼1 hr following the onset of this E79 flare, the Low Energy Telescopes (LETs) on both the STEREO A and B spacecraft observed a sudden burst of 1.6-15 MeV protons beginning hours before the onset of the main solar energetic particle event at Earth. More than 70% of these particles arrived from a longitude within ±10 • of the Sun, consistent with the measurement resolution. The deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 27 publications
7
78
0
Order By: Relevance
“…Assuming the energetic protons are effectively trapped in the shock's downstream region from r 0 to r sh , we find that the simulated 90 minute ENA fluence (black circles) at ∼2-5 MeV is twice as large as the in situ observations from STEREO (Mewaldt et al 2009). For a smaller trapping efficiency (C trap = 0.3) and a smaller source region (from (r 0 + r sh )/2 to r sh ), the simulated ENA fluence (blue circles) would be about seven times smaller than the STEREO observations.…”
Section: Simulation Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Assuming the energetic protons are effectively trapped in the shock's downstream region from r 0 to r sh , we find that the simulated 90 minute ENA fluence (black circles) at ∼2-5 MeV is twice as large as the in situ observations from STEREO (Mewaldt et al 2009). For a smaller trapping efficiency (C trap = 0.3) and a smaller source region (from (r 0 + r sh )/2 to r sh ), the simulated ENA fluence (blue circles) would be about seven times smaller than the STEREO observations.…”
Section: Simulation Resultsmentioning
confidence: 77%
“…Recently, Mewaldt et al (2009) reported that the STEREO A and B spacecraft detected 1.6-5 MeV energetic neutral atoms (ENAs) with a power-law spectrum dJ/dE ∼ E −2.46 , coming from an X9-class solar flare/CME. They suggested that these high-energy ENAs are likely produced by charge exchange of SEP protons with O 6+ ions in the high corona beyond 1.6 R S .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, energetic neutral H atoms have been observed from the solar flare of 2006 December 5 (Mewaldt et al 2009). The neutral atoms are produced by charge exchange of 1.6-15 MeV protons with atoms in the high corona.…”
Section: Type III Bursts and Impulsive Sep Eventsmentioning
confidence: 99%
“…A further channel for flare study has recently surfaced: one event (SOL2006-12-05T10:35, X9) has been found to have emitted detectable levels of energetic neutral hydrogen atoms (Mewaldt et al 2009) in the 1.8-5 MeV range.…”
Section: Solar Energetic Particlesmentioning
confidence: 99%
“…Data from nearer the Sun will help, as will improvements in our understanding of their sources. The observation of energetic neutral atoms via charge exchange (Mewaldt et al 2009) and neutrons, again from inner-heliospheric vantage points if possible, will be a major step forward. Because of the sampling issues, though, this will likely remain inthe domain of statistics rather than precise measurement.…”
Section: Future Improvementsmentioning
confidence: 99%